Gas Hydrates in Antarctica - Giustiniani, Michela (2019)
Few potential distributing areas of gas hydrates have been recognized in literature in Antarctica: the South Shetland continental margin, the Weddell Sea, the Ross Sea continental margin and the Wilkes Land continental margin. The most studied part of Antarctica from gas hydrate point of view is the South Shetland margin, where an important gas hydrate reservoir was well studied with the main purpose to determine the relationship between hydrate stability and environment effects, including climate change. In fact, the climate signals are particularly amplified in transition zones such as the peri-Antarctic regions, suggesting that the monitoring of hydrate system is desirable in order to detect potential hydrate dissociation as predicted by recent modeling offshore Antarctic Peninsula. The main seismic indicator of the gas hydrate presence, the bottom simulating reflector, was recorded in few parts of Antarctica, but in some cases it was associated to opal A/CT transition. The other areas need further studies and measurements in order to confirm or refuse the gas hydrate presence.